2016
DOI: 10.1371/journal.pone.0160753
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life (HRQoL) in Idiopathic Inflammatory Myopathy: A Systematic Review

Abstract: Health-related quality of life (HRQoL) is a research priority in chronic diseases. We undertook a systematic review (registration #CRD42015024939) to identify, appraise and synthesize the evidence relating to HRQoL in idiopathic inflammatory myopathies (IIM). A comprehensive search was conducted in August 2015 using CINAHL, EMBase and Pubmed to identify studies reporting original data on HRQoL in IIM using generic HRQoL instruments. Characteristics of samples and results from selected studies were extracted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
(99 reference statements)
2
31
1
1
Order By: Relevance
“…These included older age, effect of disease on work, the presence of another autoimmune disease, lung disease, joint involvement, and use of multiple medications. The reduction in HRQoL found in the current study is consistent with various other smaller studies that compared IIM patients to the general population , as well as analyses assessing all studies in aggregate . Other studies have shown comparable reduced HRQoL scores in other rheumatic diseases, including SLE, RA, and Sjögren's syndrome .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These included older age, effect of disease on work, the presence of another autoimmune disease, lung disease, joint involvement, and use of multiple medications. The reduction in HRQoL found in the current study is consistent with various other smaller studies that compared IIM patients to the general population , as well as analyses assessing all studies in aggregate . Other studies have shown comparable reduced HRQoL scores in other rheumatic diseases, including SLE, RA, and Sjögren's syndrome .…”
Section: Discussionsupporting
confidence: 91%
“…However, there are few sizable studies assessing HRQoL in patients with IIM . Due to the rarity of these conditions, previous studies had small sample sizes, which prohibited adequately powered statistical comparisons to delineate patient or IIM factors associated with HRQoL outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic inflammatory myopathies (IIM) are a heterogeneous group of inflammatory muscle diseases that involve muscle weakness and visceral involvement, resulting in disability and impaired quality of life [1][2][3]. As IIM are rare among inflammatory rheumatic diseases, it is difficult to collect data for outcome research with a sufficient number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Due to progressive muscular atrophy, decreasing endurance, internal organ involvement and limited therapeutic options, the disease often leads to physical disability. Several subtypes of IIM have been distinguished including among others dermatomyositis (DM), polymyositis (PM), juvenile myositis (JDM) and inclusion body myositis (IBM) [1,4]. The Health Assessment Questionnaire (HAQ) remains one of the most commonly used patient-reported outcome (PRO) tool [5,6].…”
Section: Introductionmentioning
confidence: 99%